Spectrophotometric Reaction Rate Method for the Determination of Trace Amounts of Ruthenium(III) by Its Catalytic Effect on the Oxidation of Spadns by Metaperiodate in Micellar Medium - Keyvanfard, Mohsen; Karamian, Manoochehr (Asian Journal of Chemistry, 2010)
A new, simple and highly sensitive kinetic spectrophotometric method was developed for the determination of trace amounts of Ru(III). The method is based on the catalytic effect of ruthenium(III) on the oxidation of 1,8-dihydroxy-2-(4-sulfophenylazo)naphthalene-3,6- disulfonic acid trisodium (Spadns) by metaperiodate in micellar medium at pH = 5.6. The reaction was monitored spectrophotometrically by measuring the decreasing in absorbance of Spadns at 517 nm with a fixed-time method. The decrease in the absorbance of Spadns is proportional to the concentration of Ru(III) in concentration range 0.005-0.3 mg/mL after 4.5 min from initiation of the reaction. The limit of detection is 0.36 ng/mL Ru(III). The relative standard deviation of 40.0 and 100.0 ng/mL Ru(III) was 1.7 and 2.4 %, respectively. The method was applied to the determination of ruthenium in real water samples.